2004
DOI: 10.1128/jvi.78.17.9552-9559.2004
|View full text |Cite
|
Sign up to set email alerts
|

Measles Virus Interacts with and Alters Signal Transduction in T-Cell Lipid Rafts

Abstract: By a contact-dependent surface interaction, the measles virus (MV) glycoprotein complex induces a pronounced inhibition of T-cell proliferation. We now show that MV directly interacts with glycosphingolipidenriched membrane microdomains on human primary T cells and alters recruitment and segregation of membrane proximal signaling components. Contact-dependent interference with T-cell receptor-stimulated tyrosine phosphorylation and Ca mobilization is a late event seen 24 h after MV treatment. In contrast, stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 41 publications
0
64
0
Order By: Relevance
“…Akt is regulated by Phosphatidylinositol 3-kinase (PI3K) which can be activated by the TCR coreceptor CD28 as well as the IL-2 receptor. Both pathways have been shown to be potently inhibited in the presence of MV [52,54]. At least in the context of CD28 stimulation, this effect is exerted at the levels of lipid rafts as both Akt and the PI3K regulatory subunit p85 are prevented from translocating to lipid rafts upon CD3/CD28 stimulation in primary T cells as a result of contact with MV.…”
Section: Measles Virus: Modulation From Outsidementioning
confidence: 99%
See 2 more Smart Citations
“…Akt is regulated by Phosphatidylinositol 3-kinase (PI3K) which can be activated by the TCR coreceptor CD28 as well as the IL-2 receptor. Both pathways have been shown to be potently inhibited in the presence of MV [52,54]. At least in the context of CD28 stimulation, this effect is exerted at the levels of lipid rafts as both Akt and the PI3K regulatory subunit p85 are prevented from translocating to lipid rafts upon CD3/CD28 stimulation in primary T cells as a result of contact with MV.…”
Section: Measles Virus: Modulation From Outsidementioning
confidence: 99%
“…Experimentally, T cell paralysis can be induced upon incubation of T lymphocytes with MV particles where the interaction with gp results in unresponsiveness to proliferation signals for several days, yet cells do not undergo apoptosis [50,51]. It was shown that MV contact interferes with the activation of primary T cells resulting in decreased overall tyrosine phosphorylation levels as well as Ca 2+ release upon TCR stimulation [52] and that gp contact is sufficient for specifically preventing T cells from S phase entry [51]. Interestingly, this com- plex is able to affect T cell signalling upon surface contact, which is independent of the two known entry receptors CD46 and CD150 [53].…”
Section: Measles Virus: Modulation From Outsidementioning
confidence: 99%
See 1 more Smart Citation
“…It induces expression of SIP-110, which depletes the cellular PtdIns(3,4,5)P 3 pools, suggesting that the threshold for activation signals for induction of T cell proliferation is raised (52,53).…”
Section: Lipid Phosphatases Are Exploited By Pathogensmentioning
confidence: 99%
“…Thus, measles virus infection induces an inflammatory response through alternative complement activation [205]. Measles virusinduced immnosuppression is also responsible for signal transduction alteration such as PI3K in T cell membrane rafts [206]. Tyrosine kinase-interacting protein (Tip) of lymphotropic herpesvirus saimiri (HVS) is targeted to membrane rafts in T cells and downregulates T cell receptor (TCR) and CD4 surface expression.…”
Section: Involvement Of Membrane Rafts In Virus Diseasesmentioning
confidence: 99%